Analisis Tindak Tutur Representatif pada Video Mengerti Akuntansi Tanpa Menghafal dalam Kanal YouTube Akuntan Tampan - Atiya Najal Aufa; Hikmatul Amelia; Rahma Safitri; Yolanda Pretty Nazhifa Hanun; Angelica Hexa Trinita Pandiangan; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Desy Rufaidah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
With advancements in technology, communication has become easier and more effective, especially through digital media. In the context of education, videos serve as a valuable source of information. This study aims to analyze the use of representative speech acts in the video "Understanding Accounting Without Memorization" on the Akuntan Tampan YouTube channel as a learning resource for students. Representative speech acts function to convey information clearly and convincingly. The approach used in this study is descriptive qualitative, with data collection techniques involving observation and note-taking from the video released on December 10, 2016. The researcher analyzes the patterns of speech acts used in the video, identifying types of representative speech acts that serve to explain accounting concepts in a simple and comprehensible manner for the audience, particularly for students. The analysis results indicate that there are 50 representative speech acts employed to reinforce information and aid in the understanding of accounting concepts without relying on complicated memorization methods. This research is expected to contribute to a deeper understanding of the utilization of speech acts in digital educational content. Furthermore, the findings of this study may serve as a reference for educators in enhancing the quality of learning, particularly in presenting complex material more effectively and engagingly for students.